Bahasa Inggris - Josi Noviani; Dwi Prasetyo; Dini Pusianawati; Dzulfikar Djalil Lukmanul Hakim; Setyorini Irianti (LPPM Universitas Pendidikan Mandalika, 2026)
This scoping review aims to identify and categorize pedagogical interventions designed to enhance menstrual hygiene knowledge, attitudes, and practices among adolescent girls. The study was conducted in accordance with PRISMA-ScR guidelines. Literature published between 2020 and 2026 was retrieved from PubMed, EBSCOhost, SAGE Journals, Scopus, and ScienceDirect using a Population–Exposure–Outcome (PEO) search strategy. Studies were included if they involved adolescent girls, examined menstrual hygiene education interventions, and reported outcomes related to knowledge, attitudes, or practices. Data were extracted and analyzed descriptively, and methodological quality was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Tools. The 15 included studies were predominantly conducted in South and Southeast Asia, as well as Sub-Saharan Africa. Notably, six studies employed digital approaches, while nine utilized conventional methods, reflecting a growing trend toward technology-based interventions. The interventions varied widely, including digital and mHealth-based approaches, school-based education, peer-led programs, and multicomponent strategies. Improvements were consistently reported in knowledge and attitudes, whereas changes in hygiene practices were less consistent across studies. Theoretical frameworks such as Bandura’s Social Cognitive Theory and Mayer’s Cognitive Theory of Multimedia Learning were commonly used to support intervention effectiveness. Overall, educational interventions are evolving toward more participatory and technology-enhanced models that create safe spaces for adolescents. These findings provide guidance for educational practitioners and curriculum developers in designing more effective, inclusive, and adolescent-centered menstrual hygiene education programs.